Increased TNF-α/IFN-γ/IL-2 and Decreased TNF-α/IFN-γ Production by Central Memory T Cells Are Associated with Protective Responses against Bovine Tuberculosis Following BCG Vaccination - Maggioli, Mayara F.; Palmer, Mitchell V.; Thacker, Tyler C.; Vordermeier, Hans Martin; McGill, Jodi L.; Whelan, Adam O.; Larsen, Michelle H.; Jacobs, William R.; Waters, W. Ray (Frontiers in Immunology, 2016)
Central memory T cell (Tcm) and polyfunctional CD4 T cell responses contribute to vaccine-elicited protection with both human and bovine tuberculosis (TB); however, their combined role in protective immunity to TB is unclear. To address this question, we evaluated polyfunctional cytokine responses by CD4 T cell effector/memory populations from bacille Calmette–Guerin (BCG) vaccinated and non-vaccinated calves by flow cytometry prior to and after aerosol challenge with virulent Mycobacterium bovis. Polyfunctional cytokine expression patterns in the response by Tcm, effector memory, and effector T cell subsets were similar between BCG-vaccinated and M. bovis-infected calves, only differing in magnitude (i.e., infected > vaccinated). BCG vaccination, however, did alter the kinetics of the ensuing response to virulent M. bovis infection. Early after challenge (3 weeks post-infection), non-vaccinates had greater antigen-specific interferon-γ (IFN-γ)/tumor necrosis factor-α (TNF-α) and lesser IFN-γ/TNF-α/IL-2 responses by Tcm cells than did vaccinated animals. Importantly, these differences were also associated with mycobacterial burden upon necropsy. Polyfunctional responses to ESAT-6:CFP10 (antigens not synthesized by BCG strains) were detected in memory subsets, as well as in effector cells, as early as 3 weeks after challenge. These findings suggest that cell fate divergence may occur early after antigen priming in the response to bovine TB and that memory and effector T cells may expand concurrently during the initial phase of the immune response. In summary, robust IFN-γ/TNF-α response by Tcm cells is associated with greater mycobacterial burden, while IFN-γ/TNF-α/IL-2 response by Tcm cells are indicative of a protective response to bovine TB.